2020
DOI: 10.1111/gtc.12767
|View full text |Cite
|
Sign up to set email alerts
|

H3K27me3 demethylase UTX regulates the differentiation of a subset of bipolar cells in the mouse retina

Abstract: Di‐ and trimethylation of lysine 27 on histone 3 (H3K27me2/3) is a critical gene repression mechanism. We previously showed that down‐regulation of the H3K27 demethylase, Jumonji domain‐containing protein 3 (JMJD3), resulted in a reduced number of protein kinase C (PKC)α‐positive rod ON‐bipolar cells. In this work, we focused on the role of another H3K27 demethylase, ubiquitously transcribed tetratricopeptide repeat X chromosome (UTX), in retinal development. UTX was expressed in the retinal progenitor cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A recent study also suggests that KDM6A is important for the differentiation of a subset of retinal cells. In particular, retina-specific knockout of KDM6A using Dkk3-Cre mice leads to a reduction in protein kinase C␣ (PKC␣)-positive rod "on" bipolar cells in postnatal day 10 mouse retinas while having no effect on retinal progenitor cell proliferation (39). Using a CRISPR-Cas9 KO system in C2C12 myoblasts to screen a group of candidate lysine demethylases, a group reported that KDM6A was required for osteoblast differentiation in culture (40).…”
Section: Kdm6a In Differentiation Development and Regenerationmentioning
confidence: 99%
“…A recent study also suggests that KDM6A is important for the differentiation of a subset of retinal cells. In particular, retina-specific knockout of KDM6A using Dkk3-Cre mice leads to a reduction in protein kinase C␣ (PKC␣)-positive rod "on" bipolar cells in postnatal day 10 mouse retinas while having no effect on retinal progenitor cell proliferation (39). Using a CRISPR-Cas9 KO system in C2C12 myoblasts to screen a group of candidate lysine demethylases, a group reported that KDM6A was required for osteoblast differentiation in culture (40).…”
Section: Kdm6a In Differentiation Development and Regenerationmentioning
confidence: 99%
“…[39][40][41] To determine the tissue-specific role of UTX, we generated Utx flox/flox mice and crossed them with different Cre lines. We demonstrated that UTX deficiency accelerates bladder cancer development by activating proinflammatory molecules, 42 results in decrease of PKCα-positive rod ON-bipolar cells without affecting retinal progenitor proliferation, 43 and induces hematopoietic aging by globally converting the gene expression profiles of young hematopoietic stem-progenitor cells (HSPCs) to those of aged HSPCs. 44 In this study, we aimed to clarify the role of UTX in the neural system by crossing Utx flox/flox mice with mice expressing Cre in NSPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Histone modifiers, such as the demethylases JMJD3, UTX, and LSD1, provide additional regulation. For example, the loss of JMJD3 and UTX affects the proper development of inner retinal cells such as bipolar, amacrine, and horizontal cells (Iida et al, 2014;Iwagawa et al, 2020;Umutoni et al, 2020). Lsd1 inhibition directly impacts the survival of specific retinal cells, such as RGCs and photoreceptors (Tsutsumi et al, 2016;Popova et al, 2021), and alters regulation of microRNAs, such as the miR-21-5p/NLRP12 axis, to facilitate RGC pyroptosis (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%